Social Risks of the Coal Industry Restructuring in Ukraine - Nadraga, V.І. (Економічний вісник Донбасу, 2013)
The article is devoted to the analysis of social risks of restructuring of coal industry enterprises. The risks of depressed of development of monotype settlements, unemployment, poverty are exude between the most actual, that passed from a generation to the generation. Key words: social risks, coal industry, restructuring. Стаття присвячена аналізу соціальних ризиків реструктуризації підприємств вугільної галузі. Серед найбільш актуальних виділяються ризики депресивності розвитку монопрофільних поселень, безробіття, бідності, що передаються від покоління до покоління. Статья посвящена анализу социальных рисков реструктуризации предприятий угольной отрасли. Среди наиболее актуальных выделяются риски депрессивности развития монопрофильных поселений, безработица, риски межпоколенческой передачи бедности.